How to study [ - Fry, Ronald W. (Ron Fry's How to study program, 2012)
The bestselling How to Study (Seventh Edition) reveals the study skills that all students need to know in order to be successful, whether the goal is landing a top scholarship or excelling in school. This edition includes information on how to create an effective work environment, stand out in class, use the library, conduct research online, and much more. Plus, author Ron Fry covers all the traditional elements of a winning study strategy, such as reading, writing, time-management, memory, and test-taking skills. How to Study (Seventh Edition) introduces a revolutionary study system, along with examples, that gives students the edge in any learning environment